PERAN DINAS KOMUNIKASI DAN INFORMATIKA PERSANDIAN DAN STATISTIK KABUPATEN SUMEDANG DALAM MEWUJUDKAN SUMEDANG SMART GOVERNANCE - Apriani, Delis (JRPA - Journal of Regional Public Administration, 2025)
This research aims to examine and analyze the role of the Communication and Information, Cryptography, and Statistics Office of Sumedang Regency in realizing Sumedang Smart Governance, the inhibiting factors, and the efforts to overcome these challenges. The research method used is qualitative, with data collection techniques including literature review, observation, interviews, documentation, and triangulation. Informants were selected using purposive sampling, and data analysis was carried out using the Miles and Huberman model. The results of the study indicate that the role of the Communication and Information, Cryptography, and Statistics Office of Sumedang Regency in realizing Sumedang Smart Governance has been progressing well, reflected in the development of integrated digital services such as Super Apps e-Office, e-Office Desa, Tahu Sumedang, and WAKEPO. The implementation of these programs follows relevant legislation, such as Regional Regulation No. 4 of 2024 on Digital Transformation, Presidential Regulation Number 95 of 2018 concerning Electronic-Based Government Systems (SPBE), and Law No. 14 of 2008 on Public Information Disclosure. However, several obstacles exist in the implementation, including limitations in human resources in the technology field, inadequate hardware and software infrastructure, suboptimal interoperability between applications, insufficient data security systems, and limited funding. Therefore, improvements are needed in human resource capacity, strengthening technological infrastructure, developing application interoperability standards, and enhancing data security systems to support the sustainability of Sumedang Smart Governance.